Multiple Immunosuppressive Effects of CpG-c41 on Intracellular TLR-Mediated Inflammation - Wancheng Liu; Xuejiao Yang; Ning Wang; Shijun Fan; Yuanfeng Zhu; Xinchuan Zheng; Yan Li (Mediators of Inflammation)
A growing body of literature suggests that most chronic autoimmune diseases are associated with inappropriate inflammation mediated by Toll-like receptor (TLR) 3, TLR7/8, or TLR9. Therefore, research into blocking TLR activation to treat these disorders has become a hot topic. Here, we report the immunomodulatory properties of a nonstimulatory CpG-containing oligodeoxynucleotide (CpG-ODN), CpG-c41, which had previously only been known as a TLR9 antagonist. In this study, we found that both in vitro and in vivo CpG-c41 decreased levels of various proinflammatory factors that were induced by single activation or coactivation of intracellular TLRs, but not membrane-bound TLRs, no matter what downstream signal pathways the TLRs depend on. Moreover, CpG-c41 attenuated excessive inflammation in the imiquimod-induced psoriasis-like mouse model of skin inflammation by suppressing immune cell infiltration and release of inflammatory factors. We also found evidence that the immunosuppressive effects of CpG-c41 on other intracellular TLRs are mediated by a TLR9-independent mechanism. These results suggest that CpG-c41 acts as an upstream of signaling cascades, perhaps on the processes of ligand internalization and transfer. Taken together, these results suggest that CpG-c41 disrupts various aspects of intracellular TLR activation and provides a deeper insight into the regulation of innate immunity.